Pertanggungjawaban Pidana Terhadap Pelaku Tindak Pidana Penyebaran Penghasutan Di Media Sosial Menurut Peraturan Perundang undangan Di Indonesia - Simbolon, John Freddy; Hafrida; Liyus, Herry (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
The development of information and communication technology, particularly social media, has significantly influenced patterns of social interaction, including the emergence of various forms of crime, one of which is the dissemination of incitement. This type of crime has the potential to disrupt public order and trigger social conflict if not properly addressed through adequate legal instruments. This study aims to analyze the regulation of criminal liability for perpetrators of incitement dissemination on social media under Indonesian laws and to examine future criminal law policies related to such liability. This research employs a normative legal method with statutory and conceptual approaches. The results indicate that regulations concerning criminal liability for the dissemination of incitement on social media are governed by several laws, including the Indonesian Criminal Code (KUHP) and the Law on Electronic Information and Transactions (ITE Law). However, there are still weaknesses in the application and interpretation of legal norms, particularly regarding the limits of incitement and the element of fault. Furthermore, future criminal law policies should be directed toward legal reforms that are more adaptive to technological developments, clarify the formulation of offenses, and balance law enforcement with the protection of freedom of expression. Thus, criminal liability for perpetrators of incitement dissemination on social media is expected to be implemented effectively, fairly, and with legal certainty.